2022
DOI: 10.1183/16000617.0025-2022
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer occurrence after an episode of tuberculosis: a systematic review and meta-analysis

Abstract: Introduction:People with tuberculosis experience long-term health effects beyond cure, including chronic respiratory diseases. We investigated whether tuberculosis is a risk factor for subsequent lung cancer.Methods:We searched PubMed, Scopus, Cochrane, Latin American and Caribbean Health Sciences Literature and the Scientific Electronic Library Online for cohort and case–control studies providing effect estimates for the association between tuberculosis and subsequent lung cancer. We pooled estimates through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…A review published in 2009 estimated a relative risk of 2.9 (95% CI 1.6–5.3) after controlling for lifetime tobacco smoke exposure, 18 a relative risk of 1.69 (95% CI 1.46–1.95) in a 2020 review, 13 a pooled summary estimate of 1.85 (95% CI 1.52–2.25) in a 2021 review, 16 a relative risk of 2.17 (95% CI 1.83–2.57) in a 2022 review, 14 an odds ratio of 2.09 (95% CI 1.62–2.69) in another 2022 review, 15 and finally an odds ratio of 1.74 (95% CI 1.42–2.13) in the most recent review after adjusting for age and smoking. 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review published in 2009 estimated a relative risk of 2.9 (95% CI 1.6–5.3) after controlling for lifetime tobacco smoke exposure, 18 a relative risk of 1.69 (95% CI 1.46–1.95) in a 2020 review, 13 a pooled summary estimate of 1.85 (95% CI 1.52–2.25) in a 2021 review, 16 a relative risk of 2.17 (95% CI 1.83–2.57) in a 2022 review, 14 an odds ratio of 2.09 (95% CI 1.62–2.69) in another 2022 review, 15 and finally an odds ratio of 1.74 (95% CI 1.42–2.13) in the most recent review after adjusting for age and smoking. 17 …”
Section: Discussionmentioning
confidence: 99%
“…In fact, after successful completion of PTB treatment, many individuals develop chronic respiratory complications such as abnormal lung function, 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 bronchiectasis, 11 , 12 and lung cancer. 13 , 14 , 15 , 16 , 17 , 18 These complications may result in disability and reduced health-related quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a plethora of evidence that shows the correlation of tuberculosis with lung cancer, and tuberculosis is considered an important risk factor for lung cancer [48][49][50]. Hence, targeting lung cancer with anti-tubercular compound(s) seems to be an appealing strategy and could provide a boon to a tuberculosis-infected lung cancer patient in the future.…”
Section: Cytotoxicity Analysismentioning
confidence: 99%
“…Patients with LC may exhibit deficiencies in cell-mediated immunity as either a direct effect or an indirect effect related to chemotherapy and consequently developed TB [6,27]. Some studies also reported the development of TB in LC patients [28][29][30]. So, a significant level of controversies still exists regarding the association of TB and LC which need to be explored.…”
Section: Introductionmentioning
confidence: 99%